Analisis Tarif Angkutan Penumpang Transportasi Penyeberangan Rute Tarakan – Tanjung Selor - Endah Ayu Lestari; Muhammad Djaya Bakri (Borneo Engineering : Jurnal Teknik Sipil, 2022)
Tarakan City, which is connected to Tanjung Selor by a speedboat, is one of the cities with access to maritime transportation. One form of improving speedboat services is by reviewing fares according to the ability and willingness to pay of the people. This study’s objective was to determine the fare by taking passengers willingness and ability to pay into account. The research’s methodology is based on analyses of vehicle operational costs (BOK), ability to pay (ATP), and willingness to pay (WTP). The research result, average values for the BOK, ATP, and WTP were IDR 182.386,96, IDR 165.128,25, and IDR 126.735,00, respectively. According to the ATP and WTP values, passengers had a higher ability to pay than they were willing to spend. Therefore, it is necessary to analyze the current pricing and improve the services.